PELATIHAN WIRAUSAHA DIGITAL DENGAN SISTEM BLENDED LEARNING PADA KOMUNITAS BELAJAR DARON LABS DI KOTA PADANG - Rahmi, Ulfia; Bentri, Alwen; Azrul, Azrul (UNIVERSITAS PGRI MADIUN, 2019)
Abstract. Nowadays, Indonesia is preparing for a crucial and profitable period, namely the demographic bonus which is expected to reach the point in the years of 2025-2030, but the number of unemployed are increase every year. Regarding the problem, the government has also encouraged the public to open employment opportunities with entrepreneurship. Daron Labs is a group of people who form a learning community to develop beginner entrepreneurial skills. Entrepreneurial skills transmitted by Daron Labs to prepare the community to become digital entrepreneurs, including: video makers, web designers, graphic design, and programmers. Members of this learning community are free to choose the material of interest according to the needs of each member. In this Community Service, the learning community of Daron Labs chose the location of Padang City with the consideration that the city of Padang represented the people of West Sumatra. The Daron Labs Padang community accepts members of the learning community from all community groups to develop their entrepreneurial skills. The methods offered for organizing the Daron Labs learning community through a blended learning for three months. Face-to-face meetings are twice a month and material is sent every week. Participants' responses indicate that this program is expected to continue and provide debriefing in other fields of digital entrepreneurship. Abstrak. Indonesia pada saat ini mempersiapkan diri untuk masa yang krusial sekaligus menguntungkan yaitu bonus demografi yang diperkirakan akan terjadi puncaknya pada tahun 2025-2030, namun jumlah pengangguran terus meningkat. Terkait masalah tersebut, pemerintah mendorong masyarakat membuka lapangan pekerjaan dengan berwirausaha. Daron Labs merupakan sekelompok masyarakat yang membentuk komunitas belajar untuk mengembangkan keterampilan wirausaha. Keterampilan berwirausaha yang dilakukan oleh Daron Labs untuk mempersiapkan wirausahawan digital meliputi videomaker, webdesigner, desain grafis, dan programer. Anggota komunitas belajar ini bebas memilih materi yang diminati sesuai dengan kebutuhan anggota. Pada Pengabdian kepada Masyarakat ini komunitas belajar Daron Labs memilih lokasi Kota Padang dengan pertimbangan bahwa kota Padang merepresentasikan masyarakat Sumatera Barat. Komunitas Daron Labs Padang menerima anggota komunitas belajar dari seluruh kalangan masyarakat. Metode yang ditawarkan untuk penyelenggaraan komunitas belajar Daron Labs melalui sistem blended learning yang diselenggarakan selama tiga bulan. Pertemuan tatap muka diselenggarakan dua kali dalam satu bulan dan setiap minggunya dikirimkan materi kepada peserta belajar. Respon peserta menunjukkan bahwa program ini diharapkan terus berlanjut dan memberikan pembekalan pada bidang wirausaha digital lainnya.